2016
DOI: 10.1002/pon.4197
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of professional psychological care in a large German sample of cancer patients

Abstract: Special efforts should be made to reach populations that report low utilization of psychological care in spite of having a need for support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
110
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 40 publications
7
110
3
3
Order By: Relevance
“…There is emerging evidence that the mental burden of cancer patients might be associated with increased health care utilization. Faller et al studied mental health care utilization in a sample of 4020 German cancer patients. Psychiatric disorder appeared to be a correlate of mental health care utilization (OR = 1.68) independently of symptoms of depression (OR = 1.04) and anxiety (OR = 1.08) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that the mental burden of cancer patients might be associated with increased health care utilization. Faller et al studied mental health care utilization in a sample of 4020 German cancer patients. Psychiatric disorder appeared to be a correlate of mental health care utilization (OR = 1.68) independently of symptoms of depression (OR = 1.04) and anxiety (OR = 1.08) .…”
Section: Introductionmentioning
confidence: 99%
“…Faller et al studied mental health care utilization in a sample of 4020 German cancer patients. Psychiatric disorder appeared to be a correlate of mental health care utilization (OR = 1.68) independently of symptoms of depression (OR = 1.04) and anxiety (OR = 1.08) . In addition, administrative data of 5055 heterogeneous‐cancer patients indicated that depression was associated with nonmental health care visits (OR = 1.76), emergency department visits (OR = 2.45), overnight hospitalization (OR = 1.81), and hospital readmission rates (OR = 2.03) .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, positive attitudinal aspects, knowledge, and coping concepts were important for patients with an intention (yes). Attitudinal aspects and knowledge are relevant to support‐seeking behavior . Many of these patients had precise ideas of what they wanted and would get when asking for psychooncological support, which indicates that mental health literacy, knowledge, and patient empowerment is an important aspect for service use …”
Section: Discussionmentioning
confidence: 99%
“…The need for measures that address attitudes towards help‐seeking has been highlighted as attitudes appear to be central barriers to psychological care utilisation in the context of cancer (Faller et al, ; Tondorf et al, ). To investigate the role of attitudes towards help‐seeking of German cancer patients, we translated the ASHCa into German and tested its psychometric properties in a sample of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On a socio‐demographic level, there may be a tendency for lower age and being female (Ellis et al, ; Faller et al, ; McDowell, Occhipinti, Ferguson, & Chambers, ; Zeissig et al, ) to be related with higher psychological care utilisation, but the current evidence on this is equivocal (Clover, Mitchell, Britton, & Carter, ; Tondorf et al, ). From patient self‐assessments, we know that low perceived social support (Ellis et al, ; Faller et al, ), high perceived need for help (Faller et al, ) and high distress (Clover, Kelly, Rogers, Britton, & Carter, ; Compen, Adang, Bisseling, van der Lee, & Speckens, ) are likely to be associated with higher care utilisation. When it comes to modifiable patient‐related variables, emotionally distressed individuals most frequently name attitudinal barriers as the reasons for not seeking psychosocial help (Andrade et al, ; Sareen et al, ).…”
Section: Introductionmentioning
confidence: 99%